Effect of Rutin and Telmisartam on Metabolic Syndrome X - Rajani Gunnam,; Renuka M,; Haritha K,; Swathi M,; A.B. Raju, (International Journal of Phytomedicine, 2013)
The objective of the present study was to investigate the effect of rutin and telmisartan on parameters related with insulin sensitivity, glucose and fat metabolism in the high fructose consumed animal model of the ovariectomized female Sprague dawley rats. Female Sprague Dawley (SD) rats of 180-230 g body weight were grouped and fed with either standard chow diet (NPD) or high fructose diet (HFD30% w/v). Rutin and Telmisartan were administered orally in a dose of 100 mg/kg & 5 mg/kg p.o. Daily for the entire study period. Normal parameters (Food intake & Body weight), Biochemical parameters (Blood glucose by GOD/POD method, Total Cholesterol by CHOD/PAP method, Triglyceride level, LDL, HDL) Metabolic Indicators (Aspartate transminase (AST), Alanine transminase (ALT)), Swimming test, Oral Glucose Tolerance Test, & Body weight were measured in all the groups. The unpaired t- test and analysis of variance (ANOVA) was used for statistical analysis. Telmisartan and Rutin significantly improved abnormal metabolic profile and glucose intolerance. Rutin reduces the body weight, plasma triglycerides, and total cholesterol .in addition rutin reduces the elevated serum glutamate pyruvate transminase levels. Improved abnormal metabolic profile and glucose intolerance indicates that rutin and telmisartan provides a scientific rationale for the use in metabolic syndrome.